Pengelolaan Situs Cagar Budaya Istana Rokan Dan Rumah Hulubalang Kabupaten Rokan Hulu - Shoffya Rifda Putri; Mimin Sundari Nst (Journal of Research and Development on Public Policy, 2024)
Management of the Rokan Palace Cultural Heritage Site, Rokan Hulu Regency, where this Cultural Heritage is managed by the Center for the Preservation of Cultural Values of Riau Islands Province, the Rokan Palace cultural heritage site has several problems, namely human resources that are not yet professional, lack of promotion of the Rokan Palace tourist destination, there are still too many facilities and Infrastructure in tourist destinations is damaged and inadequate, and rehabilitation budgeting is not yet optimal. The aim of this research is to describe how the Rokan Palace Cultural Heritage Site is managed and to find out the factors inhibiting the management of the Rokan Palace Cultural Heritage in Rokan Hulu Regency. This research method uses a qualitative method with a phenomenological approach. This research was conducted in Rokan Hulu Regency and in Koto Ruang Village, Rokan IV Koto District, Rokan Hulu Regency, Riau Province. There were 5 informants for this research. The type of research data used in this research is primary data in the form of data and information originating from primary sources and research informants, and secondary data in the form of documents obtained from related documents. Data collection techniques in this research are interview, documentation and observation techniques. The management of the Rokan Palace Cultural Heritage is managed by the cultural preservation center (BPK) Region IV with indicators of Planning, Organizing, Supervising and Evaluation. Then there are inhibiting factors, namely internal and external inhibiting factors. So the researchers concluded that the management was not optimal, because the Rokan Palace Cultural Heritage was still neglected, there was a lack of community participation in preserving the Rokan Palace, a lack of visits, and a lack of maximum performance by the custodian due to the lack of human resources in the management tasked by BPK.